PEMBUATAN DAN PENGUJIAN VARIASI PEMBEBANAN TERHADAP WAKTU YANG DIBUTUHKAN MESIN PEMISAH SARI PATI KEDELAI UNTUK PABRIK TAHU - Farhan, Ahmad; Ghozali, Muhamad; Novrianda, Raju; Afnanto, Nurul; Nur Rohmat, Yusup; Sukroni, Sukroni; Gunawan, Leo Van; Pradana, Claudha Alba (Jurnal Teknologi dan Riset Terapan (JATRA), 2025)
In Lohbener Village, Indramayu Regency, small and medium enterprises (SMEs) produce tofu using traditional methods, where the soybean pulp filtering process requires significant time and physical effort. To address this issue, a soybean pulp filtering machine was developed to improve filtering efficiency. The machine was tested with three different input loads—5 kg, 10 kg, and 15 kg—at a constant speed of 57 rpm. The filtering times recorded were 3 minutes 10 seconds, 5 minutes 17 seconds, and 8 minutes 21 seconds, respectively, determined by the point at which no more liquid discharged from the system. The final weights of the filtered soybean pulp were 1.5 kg, 5.7 kg, and 7.4 kg, respectively. These weight differences were influenced by an unbalanced soybean-to-water ratio, which affected extraction effectiveness. The average moisture content of the filtered pulp was 18% for the 5 kg load, 14.90% for 10 kg, and 15.17% for 15 kg. These results indicate that the use of the filtering machine significantly improves filtering efficiency compared to manual methods, in terms of time, output, and pulp quality. Overall, the machine has a positive impact on increasing productivity and product quality in tofu production at the SME level.